The Influence of Transformational Leadership and Intrinsic Motivation on Job Satisfaction and Its Impact on Employee Performance at PT Setiawan Anugerah Perkasa - Aldi Prasetio (Journal AGENCY, 2025)
This study aims to examine the influence of transformational leadership and intrinsic motivation on job satisfaction and their subsequent impact on employee performance at PT. Setiawan Anugerah Perkasa. Using a quantitative research design, data were collected from employees through a structured questionnaire and analyzed using descriptive statistics and multiple linear regression analysis. The findings reveal that transformational leadership significantly and positively influences job satisfaction, indicating that leaders who inspire, empower, and support their employees contribute to higher satisfaction levels. Intrinsic motivation is also found to significantly affect job satisfaction and employee performance, suggesting that internally driven employees demonstrate greater engagement and productivity. However, transformational leadership does not show a direct significant effect on performance, but its influence becomes substantial when mediated through job satisfaction. In contrast, job satisfaction significantly mediates the relationship between intrinsic motivation and performance, affirming its pivotal role. The study concludes that while transformational leadership may not directly improve performance, it is instrumental in enhancing job satisfaction, which in turn boosts performance outcomes. The research implies that organizations should strengthen transformational leadership practices and cultivate an environment that fosters intrinsic motivation to drive performance. Future studies are encouraged to explore additional mediating variables, such as organizational commitment or training quality, to further enrich the understanding of performance determinants within corporate settings.